THE HIGH-ALTITUDE GEOMORPHOLOGIC-LANDSCAPE DIFFERENTIATION OF THE SMALL CAUCASUS: (within the Republic of Armenia) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The principles and criteria of distinguishing the high-altitude geomorphologic- landscape zones, suh-zones and sub-zone sections are defined in this article. The main criteria of distinguishing are the value of the annual radiation balance, the quantity of the annual precipitation and its ratio, which is expressed by the value of the radiation index of dryness. The coefficient of moistening, the morphogenetic types of the relief, their qualitative and quantitative indexes are also taken into consideration. The geomorphologic and landscape features of the high-altitude zones are defined. The high-altitude limits of spreading and the occupied areas of the zones and sub-zones are shown in the table. Within the Small Caucasus we have distinguished 3 high-altitude zones and 8 sub-zones, the card- scheme of which is shown in the article.
Keywords: high-altitude geomorphologic-landscape differentiation; Small Caucasus; Republic of Armenia; high-altitude geomorphologic- landscape zones; suh-zones and sub-zone sections